2008
DOI: 10.1115/1.2950060
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Investigations of Tip Leakage Flow in Axial Flow Turbines—Part III: TIP Cooling

Abstract: Contours of heat transfer coefficient and effectiveness have been measured on the tip of a generic cooled turbine blade, using the transient liquid crystal technique. The experiments were conducted at an exit Reynolds number of 2.3×105 in a five-blade linear cascade with tip clearances of 1.6% and 2.8% chord and featuring engine-representative cooling geometries. These experiments were supported by oil-flow visualization and pressure measurements on the tip and casing and by flow visualization calculated using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
19
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…They found that the former configuration had the better thermal performance because when the ejected coolant mixed with the flow in the separation bubble, it cooled the surface of the tip both upstream and downstream of the cooling holes. Newton et al [3] also confirmed that the blowing ratio governs tip cooling. If the blowing ratio is too low, there is not enough coolant; if the blowing ratio is too high, the coolant lifted off from the blade-tip surface.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…They found that the former configuration had the better thermal performance because when the ejected coolant mixed with the flow in the separation bubble, it cooled the surface of the tip both upstream and downstream of the cooling holes. Newton et al [3] also confirmed that the blowing ratio governs tip cooling. If the blowing ratio is too low, there is not enough coolant; if the blowing ratio is too high, the coolant lifted off from the blade-tip surface.…”
mentioning
confidence: 88%
“…Using a cascade, Newton et al [3] showed that when uncooled, squealer tips have lower heat-transfer coefficients than flat tips. The cavity tip that was tested produced higher heat-transfer coefficients than the suction-side squealer tip, but lower heat-transfer coefficients than the flat tips.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…He concluded that cooling injection could cause tip clearance vortex to be reduced, and its associated losses decreased to the level observed for the case with a half gap height. Newton [9] measured the heat transfer coefficient on the tip of a generic cooled turbine blade and confirmed the reduction of heat flux to the blade tip regions. Markus [10] connected the blade leading edge and the blade tip surface using an internal channel, therefore a small part of passage flow was injected from the blade tip surface forced by the pressure difference.…”
Section: Introductionmentioning
confidence: 97%
“…And the squealer tip is a labyrinth seal structure that increases the flow resistance and introduces additional resistance to the tip leakage flow path, which has an effect of reducing the tip leakage flow. [28][29][30][31][32][33][34] A few studies about the influence of the groove depth are carried out. From the above discussion, the consideration of the tip groove depth is necessary.…”
Section: Introductionmentioning
confidence: 99%